STUDI MONITORING DEFORMASI JEMBATAN DENGAN MENGGUNAKAN TERRESTRIAL LASER SCANNER (STUDI KASUS: JEMBATAN X) - Farhan Irfanto, Muhammad
One of the efforts to monitor bridge deformation is to scan the bridge pillar structure. The deformation referred to in this study is the change in the slope of the bridge pillar caused by the relative movement of the upper bridge pillar to the lower bridge pillar from observations made at different times. The technology used in this deformation monitoring is the Terrestrial Laser Scanner (TLS). The purpose of this final project is to determine the slope of the bridge pillar structure and to analyze the reliability of the long-range type Terrestrial Laser Scanner in observing the bridge pillar slope. The methodology used to produce the slope of the bridge pillar structure includes the stages of preparation, planning, data acquisition, and data processing and presentation. The data processing process includes the stages of data classification, data filtering, slope testing, error estimation, and determination of the amount of deformation occurring from two different measurement time intervals, namely 2018 and 2020. The slope value is obtained from modeling planar fields using the regression method in point clouds bridge pillars. The results of determining the amount of deformation are presented in tables, bar charts, and pictures that can describe the direction and magnitude of the deformation. The results of this study indicate that the amount of deformation that occurs ranges from 0°0'3.257 "to 0°4'0.998" in the long section, while the large deformation obtained in the cross-section ranges from 0°0'43.318 "to 0°3'43.042". In addition, the TLS Riegl LMS-Z620 has a noise thickness of ± 2cm. The tilt compensator on the Riegl LMS-Z620 TLS can only work in vertical conditions. A tilt compensator on the TLS is very important because it can affect TLS level conditions. If the TLS is not in a level condition, then the horizontal axis of the TLS is not parallel to the level surface of the fixed point of the TLS, causing an error in the orientation of the point clouds.